Teacher Working Stress, Gender, and Workload in Pandemic Covid-19: A Correlational Study - Farah Azka Anggraeni; Zahrina Mardhiyah; Munawir Yusuf (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Changes in learning policies as the impact of the COVID-19 pandemic resulted in performance demands and different competence. Learning that was initially applied face-to- face should be carried out online by relying on creative learning media and more detailed implementation reports. As a result, the workload and responsibilities of each teacher duringthe pandemic tend to trigger heavier work stress. Stress in working is an essential factor. Proper unmanageable work stress can affect their physical, emotional, and productivity. Work stress levels can be similar or different, it depends on different genders. Therefore, the study in this paper aims to find out the relationship between work stress, workload, and the gender or primary school teachers (SD) during the pandemic in Surakarta. The samples were selected using the Cluster Random Sampling technique, which obtained 350 SD teachers. Data collection used workload scales and work stress (Refiany, 2019). The data were analyzed using Pearson’s Product Moment correlation techniques and the Mann-Whitney test for gender, which indicate that there was a significant relationship between workload and SD teacher workstress during the pandemic in Surakarta (r = 0.781, p = 0,000) and was significantly difference between the genders (p 0,035<0,05). The relationship between workload and work stress is positive. Thus, the higher the teachers’ workload is, the higher their work stress is. Workload contributes 61% to high work stress.